21st-Century Teaching Competencies, Learning Skills and Science Content Knowledge of STEM Students Among the DepEd Schools in the Province of Capiz: A Basis for Enhancement Program - Dacles , Ginalyn G. (Future Science / FSH-PH Publications, 2024)
The mixed-method research design was used to determine the level of 21st-century teaching competencies, learning skills, and science content knowledge of STEM 12 students in the province of Capiz for the school year 2023-2024. The participants of this study were the 306 STEM 12 students from a total population of 1, 446 in the province of Capiz selected through stratified random sampling using the Raosoft sample size calculator. The research instruments used in this study were the 21st-century teaching competencies questionnaire, 21st-century learning skills questionnaire, and a science content knowledge test with the demographic profile of the respondents. The questionnaires were composed of: A 70-item researcher-made 21st-century teaching competencies questionnaire; 120-item 21st-century learning skills and an 80-item science content knowledge test adopted from Competency Based Assessment – DepEd (School Division of Capiz, 2021). Another instrument used in this study was the Focus Group Discussion (FGD) Guide. It was conducted to gather qualitative data for triangulation with the quantitative data gathered. Mean, frequency, percentage, and standard deviation were used for descriptive data analysis, while analysis of variance and Pearson r were used for inferential data analysis at 0.05 level of significance. The results show that STEM 12 teachers exhibited a high level of 21st-century teaching competencies across various aspects, such as magnifying meaning, elevating experience, amplifying agency, curating curriculum, busting barriers, teaching technology, and revamping roles. Similarly, STEM 12 students demonstrate a very high level of 21st-century learning skills, with critical thinking rated as high and other skills like creativity, collaboration, communication, information literacy, media literacy, technology literacy, flexibility, leadership, initiative, productivity, and social skills rated as very high. Regarding science content knowledge, STEM 12 students were found to have a high level of understanding, with General Biology I rated as high and General Physics I rated as moderately high. Notably, the study identified significant relationships between 21st-century learning skills and teaching competencies, as well as between 21st-century learning skills and science content knowledge. However, no significant relationship was observed between 21st-century teaching competencies and science content knowledge. Based on the results, an enhancement program will be implemented to sustain and enhance the 21st-century teaching competencies of teachers, learning skills, and science content knowledge of students.